2018
DOI: 10.1101/498519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple modes of convergent adaptation in the spread of glyphosate-resistant Amaranthus tuberculatus

Abstract: The selection pressure exerted by herbicides has led to the repeated evolution of herbicide resistance in weeds. The evolution of herbicide resistance on contemporary timescales in turn provides an outstanding opportunity to investigate key questions about the genetics of adaptation, in particular, the relative importance of adaptation from new mutations, standing genetic variation, or geographic spread of adaptive alleles through gene flow. Glyphosate-resistant Amaranthus tuberculatus poses one of the most si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(127 citation statements)
references
References 62 publications
3
124
0
Order By: Relevance
“…() demonstrated multiple origins of glyphosate resistance in populations of Conyza canadensis in the Central Valley of California. Recently, multiple origins of glyphosate resistance were identified in A. tuberculatus by whole‐genome resequencing, showing both the introduction of glyphosate resistance into Canada from the USA as well as independent evolution of glyphosate resistance in other populations in Canada (Kreiner et al ., ). Others have shown that glyphosate resistance traits can be spread through hybridization between related Amaranthus species (Gaines et al ., ; Nandula et al ., ).…”
Section: Evolutionary Dynamics Of a ‘Rare’ Resistance Traitmentioning
confidence: 97%
“…() demonstrated multiple origins of glyphosate resistance in populations of Conyza canadensis in the Central Valley of California. Recently, multiple origins of glyphosate resistance were identified in A. tuberculatus by whole‐genome resequencing, showing both the introduction of glyphosate resistance into Canada from the USA as well as independent evolution of glyphosate resistance in other populations in Canada (Kreiner et al ., ). Others have shown that glyphosate resistance traits can be spread through hybridization between related Amaranthus species (Gaines et al ., ; Nandula et al ., ).…”
Section: Evolutionary Dynamics Of a ‘Rare’ Resistance Traitmentioning
confidence: 97%
“…Draft genomes have recently been obtained for some of our most important herbicide-resistant weeds, including A. tuberculatus (156), C. canadensis (157), B. scoparia (64), R. raphanistrum (158), E. crus-galli (159), and E. indica (160). Although some of these genomes are still highly fragmented, those of A. tuberculatus, C. canadensis, and E. crus-galli have N50s greater than 1.5 Mb (N50 is the length of a computationally-assembled contiguous sequence for which 50% of the sequences in an assembly are longer and 50% are shorter; longer N50 indicates a better assembly).…”
Section: Importance Of Genomics and Transcriptomics In Understanding mentioning
confidence: 99%
“…The high degree of synteny and collinearity between Angiosperms can offer insights into the genomic origin(s) of the eccDNA replicon. The eccDNA replicon was aligned to the two closely related species grain amaranth (Amaranthus hypochondriacus) and waterhemp (Amaranthus tuberculatus), each with a haploid chromosome number (n=16) and pseudochromosome-scale reference genome assemblies (Lightfoot et al, 2017;Kreiner et al, 2019). Both comparator genome assemblies have a single copy of the EPSPS gene located near the middle of scaffold 5 (Figure 3).…”
Section: Synteny and Collinearity With Amaranthus Hypochondriacus Andmentioning
confidence: 99%